2021
DOI: 10.7150/jca.48976
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress in CAR-T Cell Therapy for Hematological Malignancies

Abstract: Immunotherapies, such as monoclonal antibody therapy and checkpoint inhibitor therapy, have shown inspiring clinical effects for the treatment of cancer. Chimeric antigen receptor T (CAR-T) cells therapy was an efficacious therapeutic approach treating hematological malignancies and encouraging results have been achieved. Three kinds of CAR-T cell therapies, Kymriah (tisagenlecleucel), Yescarta (axicabtagene ciloleucel), were approved for clinical application in 2017 and Tecartus (brexucabtagene autoleucel) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 48 publications
2
86
0
Order By: Relevance
“…Activation of TLR3-promoted apoptosis of prostate cancer cells via PKC-alpha-dependent signaling in combinational therapy with 5-FU significantly increased apoptosis of human colon cancer cells [30,31]. The direct antitumor effect of TLR5 activation has been reported in 2 Journal of Immunology Research mouse xenografts of human breast cancer cells [32]. The same autocrine effect of TLR5 activation was also reported on glioma cells via NF-kappaB activation and NO production [33].…”
Section: Macrophagesmentioning
confidence: 58%
See 1 more Smart Citation
“…Activation of TLR3-promoted apoptosis of prostate cancer cells via PKC-alpha-dependent signaling in combinational therapy with 5-FU significantly increased apoptosis of human colon cancer cells [30,31]. The direct antitumor effect of TLR5 activation has been reported in 2 Journal of Immunology Research mouse xenografts of human breast cancer cells [32]. The same autocrine effect of TLR5 activation was also reported on glioma cells via NF-kappaB activation and NO production [33].…”
Section: Macrophagesmentioning
confidence: 58%
“…Checkpoint inhibitors such as anti-PD-1/PDL-1 and anti-CTLA4 antibodies that can treat solid cancers through activation of an antitumor immune response are now approved by regulatory organizations in Europe and the US [1]. Cell-based immunotherapies such as chimeric antigen receptor (CAR) T cells have also shown to be strikingly effective in treating refractory or relapsed hematopoietic malignancies [2]. These successful experiences showed that triggering an efficient antitumor immune response could be applied as an effective therapy for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In chimeric antigen receptor (CAR) T-cell therapy, T cells isolated from a patient with cancer are engineered to express tumor antigen-specific receptors that facilitate the elimination of tumor cells upon reintroduction [ 125 ]. Two CAR T-cell therapies, tisagenlecleucel (Kymriah) and axicabtagene ciloleucel (Yescarta), have been FDA-approved for hematological malignancies [ 126 ]. Rosenberg and others reported successful outcomes of ACT-TIL therapy in metastatic melanoma; these are thought to be partly due to the high acquired/somatic mutational load and the highly immunogenic nature of this cancer [ 122 , 123 , 124 , 125 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…Also, there is the risk of insertional mutagenesis caused by randomly integrating viral vectors. Moreover, in case of leukemias, blood-derived T cells might be contaminated with leukemic cells (Han, Xu, Zhuang, Ye, & Qian, 2021). Therefore, there are several manufacturing challenges that can affect the quality of CAR-T cell products (Marofi et al, 2021).…”
Section: Overview Of Car-t Cellsmentioning
confidence: 99%